Reliability and Validity of the Japanese Version of the Barriers to Access to Care Evaluation Scale Version 3 for People With Mental Disorders: an Online Survey Study - Hongo, Minako; Oshima, Fumiyo; Nishinaka, Hirofumi; Seto, Mikuko; Ohtani, Toshiyuki; Shimizu, Eiji (Frontiers in Psychology, 2021)
It is a serious problem when people with mental disorders avoid, delay, discontinue, or do not use treatment and support, despite the existence of evidence-based treatment and support methods. In this study, we aimed to clarify the factor structure of BACE v3, a scale to measure barriers to accessing mental health care, and to examine its reliability and validity among Japanese people with mental disorders. An online survey with 268 participants, 20 years old and over, who had received care from mental health services in the past 12 months was conducted. Exploratory and confirmatory factor analysis (EFA and CFA) were used to examine the structure of the BACE v3. Internal consistency and test-retest reliability of all subscales were examined. Convergent validity (correlation of one of the subscales of the BACE v3, the treatment stigma subscale with the Stigma Scale for Receiving Psychological Help (SSRPH) and with the Internalized Stigma of Mental Illness Scale (ISMI)) were assessed. EFA identified two factors (treatment stigma and non-stigma), and the results suggested that the factor structure of the Japanese version of BACE v3 was similar to the original 2-factor structure. Regarding the CFA result, the goodness-of-fit indices showed marginal fit (root mean square error of approximation = .087; Tucker–Lewis index = .842; standardized root mean square residual = .078; comparative fit index = .86). The internal consistency of the treatment stigma subscale was α = .90, and the interclass correlation coefficient was .76 (confidence interval: .70−.81). The internal consistency of the non-stigma subscale was α = .83, and the interclass correlation coefficient was .64 (confidence interval: .56−.71). The score of the treatment stigma subscale was significantly and positively correlated with the SSRPH and ISMI. Thus, the BACE v3 has acceptable consistency, reliability and validity for the assessment of barriers to accessing mental health care including treatment stigma among people with mental disorders in Japan.